2021
DOI: 10.1177/01171968211045421
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Filipino migrant workers in distress through social media platforms

Abstract: This exploratory study focuses on the Philippine government’s response to overseas Filipino workers (OFWs) in distress, especially in the Middle East using social media platforms. It examines the level of social media adoption by the Department of Foreign Affairs (DFA) in protecting Filipino nationals abroad. The popularity of social networking sites among Filipinos, including DFA officials and staff, played a vital role in influencing the institution’s move toward social media adoption. Key informant intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One of the prominent themes identified from the included studies is mental health, with several studies focusing on issues such as depression, anxiety, and other depressive symptoms among FDWs [ 72 , 75 , 89 ]. The studies aim to understand the prevalence, factors, and impacts of mental health issues on FDWs and highlight the need for appropriate support and interventions [ 28 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the prominent themes identified from the included studies is mental health, with several studies focusing on issues such as depression, anxiety, and other depressive symptoms among FDWs [ 72 , 75 , 89 ]. The studies aim to understand the prevalence, factors, and impacts of mental health issues on FDWs and highlight the need for appropriate support and interventions [ 28 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other research themes identified include social space utilization [ 12 ], minimum wages [ 13 ], cultural intelligence [ 15 ], psychological morbidities [ 28 ], reproductive health education [ 82 ], stigma [ 84 ], migration issues [ 35 , 39 ], financial implications of borrowing [ 78 ], struggles and activism [ 41 ], rehabilitation services [ 81 ], intergenerational caregiving, and childcare provision [ 63 ], subjectivities [ 55 ] and health-related behaviours [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the role of technology and social media in shaping diaspora experiences and facilitating transnational connections is an underexplored area. Given the rise of digital platforms, there is a need to examine how technology influences diaspora dynamics, identity formation, and social and economic integration (Katigbak & Roldan, 2021). Overall, these studies on labor migration and the unique experiences of Filipino professionals contribute to our understanding of the complex dynamics and implications of the Filipino diaspora.…”
Section: Literature Reviewmentioning
confidence: 99%